Development of hybrid bonded-hole hemmed joints: Process design and joint characterization. (9th June 2023) - Haran-Nogueira, A.; Kasaei, M.M.; Akhavan-Safar, A.; Carbas, R.J.C.; Marques, E.A.S.; Kim, S.K.; da Silva, L.F.M.
Abstract: This study proposes a novel hybrid joining process, called bonded-hole hemming, for joining dissimilar materials. The process combines the hole hemming process, a newly developed joining process by plastic deformation, and adhesive bonding. The suitability of this process for joining AZ31 magnesium and AA6082-T4 aluminium sheets is evaluated through finite element simulations and experimental tests, where single-lap shear testing is carried out to assess mechanical performance. The experimental and numerical analyses of the single lap joint (SLJ) tests are also performed to validate the cohesive zone model (CZM) employed in the finite element models and the phosphate-permanganate treatment (PPT) for the magnesium sheets. The results show that the pre-cured bonded-hole hemmed (BHH) joint is more advantageous than the post-cured BHH joint, due to the presence of defects in the latter, caused by uncured adhesive during the hemming stage. Both the numerical simulations, using cohesive elements, and the experimental data confirm that the hemming stage does not cause damage to the cured adhesive layer in the bonded-hole hemming process. Furthermore, the numerical simulation acceptably predicts the mechanical behaviour of the BHH joint under shear testing. In conclusion, the maximum joint strength of the BHH joints is around 11 kN, which is about 3.8 times stronger than the hole-hemmed (HH) joints (2.9 kN). According to the numerical results, it is believed that the BHH joint would exhibit enhanced strength and elongation if the tested specimens did not contain the holes used for clamping. The results allow to conclude that the bonded-hole hemming process is a viable method for joining dissimilar materials, especially those with significantly distinct mechanical properties.